LA AUTORÃA EN LA TRADUCCIÃ“N: A PROPÃ“SITO DE LA TRADUCCIÃ“N AL ESPAÃ‘OL DE WOMAN & LABOUR DE OLIVE SCHREINER - Silva-Villar, Luis; Villar, Susana Silva (European Scientific Journal, ESJ, 2015)
A close inspection of the first Spanish translation of Woman and Labour (Olive Schreiner, 1911) by Flora Osete (La mujer y el trabajo, 1914) leads us to research the circumstances that brought about its publication. The concept of authorship is revisited as well as the apparent fraud created by the substitution of the translator's name.